The Effect Of Optimization Of The Utilization Of Mother And Child's Health Book On The Attitudes Of Midwives In The Completeness Of Filling In Kia Books - Morita Wibowo; Suryo Ediyono; Heni Nur Kusumawati (Interest : Jurnal Ilmu Kesehatan, 2021)
Background: One of the efforts that have been carried out by the Ministry of Health in supporting the acceleration of MMR reduction is optimizing PONED. Apart from being poned, the use of the MCH Handbook is one way of maintaining health and obtaining quality maternal and child health services. The purpose of this study was to determine the impact of training on the optimization of the use of the MCH book on the attitudes of the PONED midwives in completing the MCH booklet filling by village midwives in the working area of ​​the Paser District Health Center. Methods: A Quantitative research method uses Quasy Experiment nonequivalent control group design. By involving 1 control group and 1 treatment group with a total sample size of 43 midwives in each group, using simple random sampling. Data analysis using Wilcoxon. Instrument that use can measure attitudes of midwives with good validity and reliability. Results: The results showed that there were significant differences in attitudes before and after treatment with a p-value of 0,000, but the mean value of attitudes before and after showed that training could not change the attitudes of midwives. The training held is not sufficient to change the attitude of midwives in compliance with the filling of the MCH handbook. Conclusion: It needs further and intense training for all PONED and non-PONED midwives and further identification is needed about things that can motivate the attitudes of midwives to improve poned midwives towards the implementation of optimization MCH books.